KELIMPAHAN ZOOPLANKTON DI PESISIR LUBUK DAMAR, SERUWAY, ACEH TAMIANG - Muhammad Zainuri; Nor Afni Fitriana; Dina Ardania; Vina Nursyarah (Journal of Aceh Aquatic Sciences, 2020)
Zooplankton has an important role in the food web, as secondary producers. Environmental changes affect the abundance and diversity of zooplankton. This study aims to examine the abundance and diversity of zooplankton in the coastal of Lubuk Damar. The research was conducted in January 2018 at Lubuk Damar coastal water, Seruway, Aceh Tamiang. Zooplankton sampling was taken at high tide, where 100 liters of water were taken using a calibrated 10-liter bucket, then filtered using a plankton net with a mesh size of 28 micron. There are nine groups of zooplankton found. The highest abundance is in Nauplius, and the lowest is in Pontilidae. A diversity index in a low state with low evenness and high dominance.